The Analysis of Politeness Strategy Used by The Main Characters in “Gifted” Film - Ayu Kadek Surya Maharani; Dewa Putu Ramendra; Ni Luh Putu Sri Adnyani (Acitya: Journal of Teaching and Education, 2023)
Politeness strategy is a strategy in the use of language related to the use of good and polite verbal communication, which can make communication work cooperatively. In terms of communicating, politeness strategies are very important to avoid conflicts in communication which means avoiding face-threatening acts (FTA) of the hearer. In researching politeness strategy, the film is a work of art that can be analyzed because it has characters and utterances that can be analyzed and are closely related to real life. Thus, a film entitled "Gifted" was chosen because this film is related to the education of gifted children, the parenting of gifted children, and is built on mental health issues in the world of learning. This study aims to analyze the politeness strategy of the main character in this film. This research used a qualitative descriptive approach and audio-visual data collection approach. The result of the analysis shows there are 60 politeness strategies data found from 512 utterances from the main characters. 37 data of positive politeness strategy categorized into three subtypes: Claim common ground (12 data), Convey that speaker and hearer are cooperators (24 data), and fulfill hearer’s want (1 data). 23 data of negative politeness strategy that categorized into: be direct (9 data), do not presume or assume (3 data), do not coerce hearer (3 data), and communicate speaker’s want to not impinge (23 data).